Which expression shows the ASSOCIATIVE PROPERTY? 3 + a + b = a + 3 + b
3(ab) = (3a)b
(3 + a) + b = 3 + (a + b)
3 - a = 3 - b

Answers

Answer 1
Answer:

Answer:

the first one

Step-by-step explanation:


Related Questions

The factors of m2 + 12m + 35 are
A trough has a semicircular cross section with a radius of 9 feet. Water starts flowing into the trough in such a way that the depth of the water is increasing at a rate of 2 inches per hour. (a) Give a function w = f(t) relating the width w of the surface of the water to the time t, in hours. Make sure to specify the domain and compute the range too.(b) After how many hours will the surface of the water have width of 6 feet?(c) Give a function t = f −^1 (w) relating the time to the width of the surface of the water. Make sure to specify the domain and compute the range too.
A faucet dripped 14 cup of water in 112 hours. What is the rate in cups per hour?
Name the vertex ot XYZ.
Gabriella swims 2 laps per minute. What is the associated rate? ___ minute per lapA.2B.4C.1/4D.1/2ANSWER QUICKKK

there are 650 students in a school if the number of girls is 106 more than the boys how many boys are in the school​

Answers

There are 272 boys in the school

Answer:

boys = 272

Step-by-step explanation:

b = boys

g = girls

1) write two equations with the given informations:

g + b = 650

g = b + 106

2) substitute the value of g in the first equation:

b + 106 + b = 650

3) solve the equation for b

2b = 544

b = 272

4) substitute the value in the second equation

g = 272 + 106

g = 378

girls = 378

boys = 272

-2(bx-5)=16 what is the value of x in terms of b and what is the value of x when b is 3?

Answers

Answer= -54



-2(bx-5)=16

If b is 3, then it changes to -2(3x-5)=16

We want to find x, right? Then we must do -2•3x and -2(-5). The result would be -6x and 10.

Then again, the equation would change -6x+10=16
Which would be -6x=6
Is x=6/6

And then x would be 1


Please tell me what I did wrong and if it is wrong, comment on this and I’ll fix my mistake!^^

Keith has a bag of Skittles. He is trying to get Jashawn to figer out how many Skittles are in his bag. There are 16 red. 25% of the bag is orange. 1/8 of the skittles are yellow. Tge rest of the skittles are green.If 2/5 of the bag is red,how many skittles are in the bag? How many skittles are orange? How many of the skittles are green?

Answers

Answer:

Total number of skittles in bag are 40

There are 10 orange skittles.

There are are 9 green skittles.

Step-by-step explanation:

Suppose there are "x" number of skittles in the bag.

Given that 2/5 of x = 16

Solving above equations gives , x = 40

That means total numbers of skittles are 40.

2/5 of 40 = 16 red skittles.

25 % of 40 = 10 orange skittles

1/8 of 40 = 5 yellow skittles

40-16-10-5 = 9 green skittles.

The function f(x) = 2x2 + 3 represents the rate of a boat traveling with the current in miles per hour. The function g(x) = x + 2 represents the time the boat traveled in hours. Solve (f • g)(2), and interpret the answer.

Answers

\boxed{(f\cdot g)(2)=44}

Explanation:

Here we have two functions, namely:

f(x)=2x^2+3 \n \n \n g(x)=x+2

So here we need to perform the product of two functions and evaluate this new function for x=2. So:

f(x)=2x^2+3 \n \n g(x)=x+2 \n \n \n (f\cdot g)(x)=(2x^2+3)(x+2) \n \n (f\cdot g)(2)=(2* 2^2+3)(2+2) \n \n \boxed{(f\cdot g)(2)=44}

Learn more:

Rigid transformations:brainly.com/question/13653482

#LearnWithBrainly

Answer:

C.(f • g)(2) = 44, the distance in miles the boat traveled

Step-by-step explanation:

Select the correct answer.
Which of these sentences is always true for a parallelogram?

Answers

Answer:

Letter D

Remember to drink water

Answer:

parallelograms are shapes that have 2 sets of parallel sides. for example, squares, rectangles, and rhombuses are all types of parallelograms

Plz help me simply this

Answers

Answer:

Step-by-step explanation:

\sqrt[5]{u^(10)*p^(15)}*\sqrt[4]{u^(16)*p^(18)}=  \sqrt[5]{u^(2*5)*p^(3*5)}*\sqrt[4]{u^(4*4)*p^(16*2)}\n\n\n=\sqrt[5]{(u^(2))^(5)*(p^(3))^(5)}*\sqrt[4]{(u^(4))^(4)*p^(4*4)*p^(2)}\n\n=\sqrt[5]{(u^(2))^(5)*(p^(3))^(5)}*\sqrt[4]{(u^(4))^(4)*(p^{4)^(4)}*p^(2)}\n\n=u^(2)*p^(3) * u^(4)*p^(4)*\sqrt[4]{p^(2)}\n\n=u^(2+4)*p^(3+4)*\sqrt[4]{p^(2)}\n\n= u^(6)p^(7)\sqrt[4]{p^(2)}